2009
DOI: 10.1021/la902340z
|View full text |Cite
|
Sign up to set email alerts
|

Acute Degradation of Surface-Bound Unsaturated Polyolefins in Common Solvents under Ambient Conditions

Abstract: We describe the detachment of covalently grafted polybutadiene and polynorbornenechains -which were prepared by surface-initiated ring-opening metathesis polymerization (SiROMP) -from Si/ SiO 2 substrates upon brief exposure to common solvents in air. Degradation and disappearance of grafted polybutadiene films after successive rinses with dichloromethane was monitored by ellipsometry. Changes in surface topography were analyzed by atomic force microscopy. The rapid auto-oxidation of allylic carbon-hydrogen bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…However, sulfide linkers are susceptible to oxidation, leading to both discoloration and degradation over time. The disadvantage of using amine nucleophiles to displace chloride on PVC is that amines are also excellent bases, leading to inevitable competitive elimination, resulting in unsaturation in the polymer chain and consequent low thermal stability . Another method to attach plasticizers to PVC is copper‐catalyzed azide‐alkyne cycloaddtion .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sulfide linkers are susceptible to oxidation, leading to both discoloration and degradation over time. The disadvantage of using amine nucleophiles to displace chloride on PVC is that amines are also excellent bases, leading to inevitable competitive elimination, resulting in unsaturation in the polymer chain and consequent low thermal stability . Another method to attach plasticizers to PVC is copper‐catalyzed azide‐alkyne cycloaddtion .…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantage of using amine nucleophiles to displace chloride on PVC is that amines are also excellent bases, leading to inevitable competitive elimination, resulting in unsaturation in the polymer chain and consequent low thermal stability. 29 Another method to attach plasticizers to PVC is coppercatalyzed azide-alkyne cycloaddtion. [30][31][32][33][34][35][36][37][38] However, the use of a copper catalyst leaves a toxic copper residue.…”
mentioning
confidence: 99%
“…A later study by Chen et al reported that surface-grafted polybutadiene (PBd) and polynorbornene (PNb) brushes suffered acute degradation upon solvent rinsing under ambient conditions, leading to the decrease in film thickness [152]. The degradation was ascribed to the rapid auto-oxidation of allylic carbon-hydrogen bonds, supported by an earlier work by Jennings and co-workers which demonstrated that the loss of PNb films was probably caused by the cleavage of polymer chains at the olefin sites [153] and the control experiment that degradation of PBd film did not occur when solvent rinsing was carried under nitrogen in a glovebox.…”
Section: Neutral Polymer Brushesmentioning
confidence: 99%
“…24,25 We showed that carrying out SiROMP of COD in the vapor phase is a viable approach in grafting polybutadiene (PBd) on Si/SiO 2 substrates, yielding ~ 10 nm thick films after 30 min of polymerization time at room temperature. Commonly, ROMP of low-strain cyclic olefins is complicated by competing chain transfer reactions.…”
Section: Introductionmentioning
confidence: 99%